Enhancing Employee Performance through Motivation, Work Environment, and Training: Evidence from PT Medcomm Solution - Gulo, Natanael; Purba, Purnama Yanti; Adelia, Adelia; Manik, Marieni; Simarmata, Hengki Mangiring Parulian (Economics and Digital Business Review, 2026)
The goal of this study is to look into how work motivation, the work environment, and training affect how well employees do their jobs at PT Medcomm Solution. In service organizations, human resources are regarded as a strategic element affecting performance, with other internal organizational factors contributing. This study utilized a quantitative methodology with a causal associative research design. The sample encompassed all 60 employees, employing a census sampling methodology. The data were analyzed using multiple linear regression. The findings suggest that job motivation and training positively and significantly influence employee performance, however the work environment does not. These three independent factors have a substantial effect on employee performance at the same time, as shown by the F-value of 20.085 and the significance level of 0.000 (<0.05). The coefficient of determination value of 51.8% shows that the variables of work motivation, work environment, and training can explain differences in employee performance. The other 48.2% is due to factors not included in this research model, such as rewards, pay, work discipline, organizational culture, job satisfaction, work stress, and individual employee characteristics.